2014
DOI: 10.1016/j.stemcr.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Bright/Arid3A Acts as a Barrier to Somatic Cell Reprogramming through Direct Regulation of Oct4, Sox2, and Nanog

Abstract: SummaryWe show here that singular loss of the Bright/Arid3A transcription factor leads to reprograming of mouse embryonic fibroblasts (MEFs) and enhancement of standard four-factor (4F) reprogramming. Bright-deficient MEFs bypass senescence and, under standard embryonic stem cell (ESC) culture conditions, spontaneously form clones that in vitro express pluripotency markers, differentiate to all germ lineages, and in vivo form teratomas and chimeric mice. We demonstrate that BRIGHT binds directly to the promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…4D). These characteristics are all features specific to PV neurons (17). At 7-10 dpi, spontaneous action potentials were detected and could be abolished by TTX (Fig.…”
Section: Identification Of Forskolin As a Promising Candidate For Ipvmentioning
confidence: 72%
“…4D). These characteristics are all features specific to PV neurons (17). At 7-10 dpi, spontaneous action potentials were detected and could be abolished by TTX (Fig.…”
Section: Identification Of Forskolin As a Promising Candidate For Ipvmentioning
confidence: 72%
“…We previously showed that ARID3a enhances transcription of a subset of IgH promoters after B cell activation (11–14, 43, 44), and that it can act as a repressor of pluripotency genes, including Oct4, in somatic cells (45, 46). However, the gene targets and mechanisms by which ARID3a functions in HSPCs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function studies revealed that >98% of Arid3a À/À mice die prior to embryonic day 11.5 (E11.5) (Webb et al 2011), suggesting a potential role in embryonic development. A recent follow-up study showed that singular loss of Arid3a is sufficient for reprogramming as well as enhancement of standard four-factor reprogramming of mouse embryonic fibroblasts (MEFs) to fully induced pluripotent stem cells (Takahashi and Yamanaka 2006;Popowski et al 2014). That Arid3a is expressed highly in extraembryonic trophoblast lineages that give rise to the placenta (Wu et al 2009) led us to examine its function in ES cells and TE lineage commitment and differentiation.…”
Section: Cdx2mentioning
confidence: 99%